Comparative transcriptomic analysis of Listeria monocytogenes reveals upregulation of stress genes and downregulation of virulence genes in response to essential oil extracted from Baccharis psiadioides - Pieta, Luiza; Escudero, Frank Lino Guzman; Jacobus, Ana Paula [UNESP]; Cheiran, Kamila Patikowski; Gross, Jeferson [UNESP]; Moya, Maria Lisseth Eguiluz; Soares, Geraldo Luiz Gonçalves; Margis, Rogério; Frazzon, Ana Paula Guedes; Frazzon, Jeverson (Springer Nature, 2017)
Listeria monocytogenes is a pathogenic microorganism in humans and is frequently transmitted by food. Methods to control the presence of Listeria in foods are necessary. In the present study, transcriptomics of L. monocytogenes grown in the presence of essential oil extracted from Baccharis psiadioides were studied by RNA sequencing and reverse transcription quantitative polymerase chain reaction (RT-qPCR) experiments. The results obtained indicate that essential oil of B. psiadioides has potential bacteriostatic activity at the concentration tested, affecting Listeria cells functioning and development. Responses of the microorganism included upregulation of stress genes and downregulation of virulence genes, such as actA, hly and prfA, indicating a decrease in virulence and in the capacity of the microorganism to cause infection. Thus, the results presented here allow us to conclude that B. psiadioides essential oil may be an alternative means of controlling microorganisms proliferating in foods.
Keywords: Bacteriostasis; Essential oil; Listeria monocytogenes; RNA sequencing; RT-qPCR; Virulence